Chromium and fluoride contamination in groundwater around leather tanning industries in southern India: Implications from stable isotopic ratio δ53Cr/δ52Cr, geochemical and geostatistical modelling. (April 2019) - Kanagaraj, G.; Elango, L.
Abstract: This study investigates the contamination of groundwater by chromium and fluoride around leather tanning industries. Major ions, chromium, δ 53 Cr/δ 52 Cr and fluoride were analyzed by advanced analytical methods. High degree of variation was observed in the concentration of chloride in groundwater, which ranged between 205 and 3310 mg/L, around 56% of the samples were recorded above the acceptable limit indicating the quality of groundwater is fresh to saline and it could be due to mixing of tannery effluents with freshwater aquifers. The chromium in the groundwater around 40% of the sampling wells exceeds the permissible limit whereas, 37% of wells were with fluoride above the accepted limit. Geochemical modelling using Phreeqc suggest that the saturation index of minerals such as calcite, dolomite, fluoride, gypsum and anorthite is affected by precipitation, dissolution and ion exchange processes. Concentration of chromium isotopes δ 53 Cr and δ 52 Cr reveals the source of Cr in the groundwater is more likely from tannery effluents. Accumulation of fluoride in groundwater is contributed by bedrock, charnockite, granite, epidote hornblende gneiss, fissile hornblende biotite gneiss in the study area. Groundwater contamination in this area is caused by both natural as well as anthropogenic sources. Around 37% of the samples exceeds HQI limit (HQI>1), which indicates possible health problems to the public upon prolonged use of untreated groundwater for drinking. To overcome this situation, it's essential to improve the performance of the effluent treatment plants and recharge structure to recover the quality of groundwater. Graphical abstract: Image 1 Highlights: Chromium and fluoride are in high concentration in groundwater. Isotopic ration δ 53 Cr/δ 52 Cr indicates natural and anthropogenic sources. Geostatistical modelling through EBK assists in better interpolation. Human health risk is high in the study area.